What Do Anesthesiologists Know about p Values, Confidence Intervals, and Correlations: A Pilot Survey - Patrick Schober; Sebastiaan M. Bossers; Phi-Vu Dong; Christa Boer; Lothar A. Schwarte (Anesthesiology Research and Practice)
Background. Statistical methods form the basis for clinical decision-making in evidence-based anesthesia. Data on the knowledge of anesthesiologists about statistics are lacking. This pilot study aims to provide a first impression of the anesthesiologists’ understanding of commonly used concepts in statistics. Methods. A cross-sectional pilot survey was performed at a major international anesthesia conference. The questionnaire consisted of three basic multiple-choice questions on the topics “p value,” “confidence interval,” and “correlation.” Results of the questions are reported as percentage of correct answers (95% confidence interval). Results. 65 questionnaires were analyzed. Forty participants were male, and mean age was 40 (standard deviation: 10) years. The question addressing the p value was correctly answered by 15% (95% CI: 8 to 27%) of respondents. The question concerning the 95% confidence interval was answered correctly by 28% (95% CI: 18 to 40%) of participants. For the question about correlation, a correct answer was given by 52% (95% CI: 40 to 64%). None of the participants answered all questions correctly, and 19 participants provided a wrong answer to all questions. Conclusions. Anesthesiologists seem to demonstrate a poor understanding of statistical key concepts. Further studies are needed to address statistical knowledge gaps among anesthesiologists more comprehensively.